The intermediary in the criminal justice system - Taggart, John (Writer on criminal justice) (Routledge, 2026)
"This book undertakes a sociolegal examination of the intermediary role within the criminal jus-tice system. The intermediary special measure is one of the most innovative and controversial developments in the history of English criminal procedure. But what does the role actually involve? That is the central question explored in this book. Despite increased academic attention into this new criminal justice actor, the content of the intermediary role remains unclear. Based centrally on empirical data gathered in England and Wales and Northern Ireland, but also drawing upon comparative material from other jurisdictions, the book examines how those executing the role of intermediary understand its work and how other criminal justice actors perceive it. The book then uses this as the basis for generating a theory of the intermediary role, and its scope and content. It also considers the future of the role and its integration into the criminal justice sys-tem. This book will appeal to those researching and studying in the areas of sociolegal studies, crim-inal law and criminology, as well as lawyer, judges, intermediaries and policy makers working in relevant areas"-- Provided by publisher.